Modelagem da dinâmica do processo de transição epitélio-mesenquimal em câncer - Silveira, Daner Acunha (2021)
The epithelial-mesenchymal transition (TEM) is a fundamental cellular process based on the conversion of epithelial cells into mesenchymal cells, which plays an essential role in the dissemination of cancer through metastasis. The evolution of knowledge in terms of the molecules and interactions that govern the complex TEM system has required the use of computational approaches that provide non-intuitive results on the complexity of its dynamics. Thus, this study aims to analyze recent biochemical information published in the literature through logical computational modeling in order to amplify the dynamic knowledge of the transition. The two proposed models are related to TEM activating molecule TGF-β. The data were compared with theoretical and experimental data for MCF10A human breast epithelial cell line presenting excellent agreement. Collectively, the results demonstrated the functionality of the circuits during the transition and, thus, microRNAs 129, 340 and 1199 may be considered factors of phenotypic stability of the hybrid state. Additionally, the data revealed the phenotypic probabilities in the coexistence region and demonstrated that the hybrid state is the most probable in the tristable dynamics, agreeing with experimental data. Therefore, the present study highlights new mechanisms related to the dynamics of TEM in response to the TGF-β molecule in breast epithelial cells and such results help to improve new therapeutic strategies for breast cancer.